Hubungan IPK dan Nilai Pretest Terhadap Hasil OSCE Mahasiswa pada Mata Kuliah Praktikum Farmakologi - A’laTarigan, Abul; Chaizuran, Meutia; Maria Ladia PS, Siti; Zulkarnaini, Zulkarnaini (Pustaka Galeri Mandiri, 2025)
Undergraduate nursing education requires graduates to be competent both theoretically and practically, particularly in pharmacology practicums. Although students may have strong theoretical knowledge, their practical skills as measured by the Objective Structured Clinical Examination (OSCE) often differ. This study aimed to evaluate the relationship between Cumulative Grade Point Average (GPA) and pretest scores with OSCE results among pharmacology practicum students. A cross-sectional design was conducted involving 146 second-semester students at the Faculty of Nursing, Syiah Kuala University. Data collected included GPA, pretest scores, and OSCE scores. Descriptive analysis and Spearman correlation were used to examine the relationships between variables. The majority of students were female (93.8%) and 19 years old (53.4%). The mean GPA was 3.64 ± 0.14, pretest score 86.95 ± 4.89, and OSCE score 67.31 ± 4.27. There was a significant positive correlation between GPA and OSCE (r = 0.165, p = 0.047) and between pretest and OSCE (r = 0.836, p < 0.01). The correlation between pretest and OSCE was stronger than that of GPA, indicating that prior knowledge plays a dominant role in achieving practical skills. Mastery of theoretical knowledge through pretests significantly influences students’ practical skills. Pharmacology practicum learning strategies should emphasize the integration of theory and practice, including pretest reinforcement, simulation, and structured clinical training, to enhance students’ competence in OSCE.